The effect of window proportions in low-rise residential buildings on annual energy consumption in humid temperate climate (case study: Rasht city in Iran) - Bagheri, Sara; Moradinasab, Hossien; Yeganeh, Mansour (Frontiers in Energy Research, 2024)
The proportions of exterior windows in low-rise residential buildings are crucial for optimizing energy consumption. This study investigates and optimizes these proportions for buildings in the temperate climate of Rasht City, Iran. A building was simulated in DesignBuilder software to explore how different window-to-wall ratios affect energy consumption. Using a parametric algorithm, the percentage of windows on each building facade was varied from 10% to 100%, and heating, cooling, and lighting loads were calculated. The results revealed that optimizing window proportions can significantly reduce annual energy consumption. For the north-facing facade, the optimal window-to-wall ratio is between 26% and 33%. On the south side, the most efficient window proportion is 21-25%, resulting in the lowest energy consumption of 2102 kWh/m² per year. The optimal window proportions for the east and west facades are 54-57% and 58%, respectively. The study found a strong correlation between energy consumption and the windowto-wall ratio for the south-facing facade, with a correlation coefficient of 0.97. For the north, east, and west facades, the correlation coefficients are 0.72, 0.17, and 0.33, respectively. These findings can predict energy consumption for residential buildings in Rasht and similar climates. Optimizing window proportions is an effective strategy to reduce energy use and enhance residents' quality of life, applicable to both new constructions and renovations of existing buildings.